KETERSEDIAAN KOLEKSI MUATAN LOKAL DI PERPUSTAKAAN SMA/SMK DALAM MENINGKATKAN LITERASI BUDAYA SISWA DI KOTA PEKANBARU - Sondra, Aivan; Amelia, Vita; Hakim, Triono Dul (UIN Imam Bonjol Padang, 2024)
This article discusses the availability of library collections related to the local content curriculum of Malay culture. The Riau Malay culture local content curriculum has been started for a long time in Riau and especially in Pekanbaru. Every year the quality of the curriculum and teaching staff also continues to be improved. This should also be supported by the availability of collections in school libraries to support learning and support the successful implementation of the local content curriculum at the Senior High School level. The sample of this study came from 15 randomly selected schools, namely 9 high schools and 6 vocational schools spread across the city of Pekanbaru. The results show that for the high school category, for each grade level, namely class X, class XI and class XII, the library has all the handbooks in the form of compulsory handbooks of Malay Culture subjects. But for SMK, each school is different, in general only class X and Class XI are still studying Malay Culture. For class XII it is no longer because students focus on school vocational subjects. For supporting collections, it is still dominated by book collections. In terms of the number of collections in general, it does not meet the needs, so the library makes it a reference collection. In terms of titles, it has seen diversity, it's just that some schools only have package books / handbooks for teachers and students without having reference books to support subjects.